Evaluation of Recurrent Lymphadenitis after Six Months Anti-Tuberculous Therapy - Hasan Chowdhury, Mohammad Mainul; Chowdhury, M A Jalil; Kamal, S M Mostofa; Anam, M Khairul; Islam Khan, M Touhidul; Zohura, Fatima Tuj (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Recurrence or persistence of tuberculous lymphadenitis even after treatment occurs due to paradoxical immune response, non-tubercular mycobacterial (NTM) infection, drug resistance tuberculosis or because of misdiagnosis. In these situations sometimes the patients are asked to continue category-1 more than six months on the basis repeat fine needle aspiration cytology (FNAC) findings. This study evaluated the cause of persistence or appearance of new lymph node after anti-TB category-1. Methods: This observational study was done from January, 2013 to March, 2014 after getting ethical clearance from Bangabandhu Sheikh Mujib Medical University (BSMMU). Patients who had persistent or new lymphadenitis after completing anti-TB category-1 for six months were selected. After analysis of treatment records, patients were selected for either FNAC or biopsy with local surgical clearance. Cyto/histopathological analysis, AFB stain (LED fluorescent), AFB culture (MGIT and L-J media) and GeneXpert test was done. Follow-up of the patients were done after two weeks and six months of FNA/surgery. Results: Thirty-two patients (M/F=11/21) with mean age 25(±12) years were investigated. Altogether 26 cases (81.25%) Journal of Bangladesh College of Physicians and Surgeons Vol. 41, No. 4, October 2023 were confirmed as tuberculous lymphadenitis and six (18.75%) were non-tuberculous (03 lymphomas, 01 sarcoidosis, 01 reactive lymphadenitis and 01 pyogenic abscess). Among the TB patients, granuloma was present in 23 cases (88.46%) (FNA-07, biopsy-16). Twenty-three (88.46%) cases were GeneXpert positive, comprising 21 rifampicin sensitive and 02 rifampicin resistant. One rifampicin resistant case was confirmed by culture and the remaining 25 were culture negative. One case was AFB stain positive and no NTM was found in AFB culture. After surgery, rapid healing was observed within two weeks among tuberculous lymphadenitis patients. Conclusions: Persistent granuloma after anti-TB category-1 does not indicate active tuberculosis if it is culture negative. It may occur due to immunological reaction against dead bacilli in deep seated sinus. Local surgical clearance results rapid recovery and other diagnosis should be excluded without further continuation of anti-TB category-1. J Bangladesh Coll Phys Surg 2023; 41(4): 262-268